Implementation and Evaluation of Static Code Analysis to Identify Security and Code Quality Issues in Academic Information Systems - Ramdani, Cecep Muhamad Sidik; Shofa, Rahmi Nur; Anshary, Muhammad Adi Khairul; Gufroni, Acep Irham; Yahya, Aria Priawan; Fazamin Bin Wan Hamzah, Wan Mohd Amir (Jurnal Teknik Informatika (Jutif), 2025)
In today's digital era, websites have become a key component of various digital services, from government and education to business. However, many security incidents occur due to undetected source code vulnerabilities, such as vulnerabilities, bugs, and code smells, which can degrade system performance and reliability. Therefore, a systematic approach is needed to detect and prevent these issues as early as possible. This study aims to implement and evaluate the effectiveness of the Static Code Analysis (SCA) method in identifying security and code quality issues in web applications. The tool used was SonarQube, which was then implemented in the SIMAK Universitas Siliwangi. Evaluation and testing were conducted on the tool's ability to detect various types of problems, its level of accuracy, and its ease of integration into the software development process. In this study, the evaluated aspects were bugs, code smells, and vulnerabilities. The results of this study found 23,241 issues, consisting of 2,356 bugs and 20,885 code smells, without any vulnerabilities found. With a problem ratio of 3.84% of the total code lines of 605,130, and a severity classification dominated by issues at the Critical and Major levels, these results provide an overview of the technical condition of the code used in SIMAK Universitas Siliwangi. This research is expected to provide practical contributions for software developers and security teams in continuously improving the quality and security of web applications. The outcomes of this study are expected to offer substantial and actionable contributions toward advancing the overall quality, robustness, and security of software systems. By strengthening these foundational aspects, the research is projected to positively influence the reliability, continuity, and long-term sustainability of academic service delivery within higher-education environments.